Five years on: Influences on early career health professionals from a rural interprofessional pre‐registration immersion program. (1st April 2021) - Pullon, Susan; Garrett, Susan; Garnett, Amanda; Schwass, Elizabeth Rose; McKinlay, Eileen; Ashworth, Natasha; Darlow, Ben
Abstract: Objective: To ascertain former students' perceptions of and influences from a final‐year pre‐registration, rurally located, clinically based, 5 week interprofessional program on their subsequent work and career in the health professions. Design: Online survey delivered 5 years post‐program (4 years post‐graduation). Setting: The Tairāwhiti interprofessional education program was first undertaken in 2012/2013 by students from six health professional degree programs (dentistry, dietetics, medicine, nursing, pharmacy and physiotherapy) in the Tairāwhiti region, New Zealand. Participants: Health professionals who attended the Tairāwhiti interprofessional education program in 2012/2013 as students were invited to participate; 70 of 86 (81%) responded in 2017/2018. Results: Five years on, most respondents (91%;64/70) were working as health professionals, with a fifth (23%;15/64) working overseas. Of those currently practising in New Zealand, 51% (24/47) were working in hospital practice and 49% (23/47) in the community, with 56% (27/48) working in metropolitan areas and 44% (21/48) in regional/rural locations. Of the 51 respondents who provided free‐text comments about perceived influences of program participation, the majority described positive influences on their clinical practice as health professionals or their subsequent career choices. Five themes emerged from the free‐text data: 'made me a better clinician'; 'made me consider rural/regional work'; 'collaborating for care'; 'choosing an area of practice to work in, ' and 'little or no impact.' Conclusion: This work reports positive influences on subsequent careers among respondents who had previously participated as final‐year students in a rurally located IPE program, particularly with respect to interprofessional working, rural health, and contextual and cultural influences.